Clinical Evaluation of Tumour Marker Combinations in the Differential Diagnosis of Benign and Malignant Liver Disease. Issue 1 (1991) - Lucarotti, M. E.; Rothnie, N. D.; Kelly, S. B.; Hershman, M. J.; Johanssen, C.; Nilsson, O.; Lindholm, L.; Wood, C. B.; Williamson, R. C. N.; Habib, N. A.
Abstract : CEA, CA19-9 and CA50 are tumour associated antigens defined by monoclonal antibodies which have been raised against adenocarcinoma cell lines. The aim of this study was to determine whether their combined use could improve diagnostic accuracy in patients with primary and secondary liver tumours. An immunoradiometric assay was used for the detection of CEA and CA19-9 and the Delfia system for CA50. Serum was collected from 65 normal subjects, 40 with hepatobiliary carcinoma (26 primary, 14 secondary) and 17 with benign hepatobiliary disease. The cut-off levels were calculated as the mean of the control group plus 2 standard deviations. All three antibodies contributed to improving the correct classification of secondary liver tumours (multivariant discriminant analysis p<0.05), but only CA19-9 and CA50 contributed to the diagnosis of primary liver tumours (multivariant analysis p<0.05). The diagnostic accuracy versus benign disease was 81% for primary carcinoma and 91% for secondary carcinoma. Combined use of CEA, CA19-9 and CA50 helps to differentiate benign from malignant hepatobiliary disease.